Brain Changes in Responders vs. Non-Responders in Chronic Migraine: Markers of Disease Reversal - Hubbard, Catherine S.; Becerra, Lino; Smith, Jonathan H.; DeLange, Justin M.; Smith, Ryan M.; Black, David F.; Welker, Kirk M.; Burstein, Rami; Cutrer, Fred M.; Borsook, David (Frontiers in Human Neuroscience, 2016)
The aim of this study was to identify structural and functional brain changes that accompanied the transition from chronic (CM; ≥ 15 headache days/month) to episodic (EM; < 15 headache days/month) migraine following prophylactic treatment with onabotulinumtoxinA. Specifically, we examined whether CM patients responsive to prophylaxis (responders; n = 11), as evidenced by a reversal in disease status (defined by at least a 50% reduction in migraine frequency and < 15 headache days/month), compared to CM patients whose migraine frequency remained unchanged (non-responders; n = 12), showed differences in cortical thickness using surface-based morphometry. We also investigated whether areas showing group differences in cortical thickness displayed altered resting-state functional connectivity (RS-FC) using seed-to-voxel analyses. Migraine characteristics measured across groups included disease duration, pain intensity and headache frequency. Patient reports’ of headache frequency over the four weeks prior to (pre-treatment) and following (post-treatment) prophylaxis were compared (post minus pre) and this measure served as the clinical endpoint that determined group assignment. All patients were scanned within two weeks of the post-treatment visit. Results revealed that responders showed significant cortical thickening in the right primary somatosensory cortex (SI) and anterior insula, and left superior temporal gyrus and pars opercularis compared to non-responders. In addition, disease duration was negatively correlated with cortical thickness in fronto-parietal and temporo-occipital regions in responders but not non-responders, with the exception of the primary motor cortex (MI) that showed the opposite pattern; disease duration was positively associated with MI cortical thickness in responders versus non-responders. Our seed-based RS-FC analyses revealed anti-correlations between the SI seed and lateral occipital (LOC) and dorsomedial prefrontal cortices in responders, whereas non-responders showed increased connectivity between the pars opercularis seed and LOC. Overall, our findings revealed distinct morphometric and functional brain changes in CM patients that reverted to episodic migraine following prophylactic treatment compared to CM patients that showed no change in disease status. Elucidating the CNS changes involved in disease reversal may be critical to discovering interventions that prevent or slow the progression of CM. Such changes may aid in the evaluation of treatments as well as provide markers for disease ‘de-chronification’.